The Influence of Product Quality, Promotional Mix, and Location on Consumer Satisfaction at Medan Kerang Hore Crab - Riovani Leandra Ibaneza; Muhammad Ebuziyya Alif Ramadhan; Eru Ahmadia (Electronic Journal of Education, Social Economics and Technology, 2026)
This study aims to analyze the influence of product quality, promotional mix, and location on customer satisfaction at Medan Kerang Hore Crab in Pontianak City. The study employs a quantitative approach with an associative research design. The research sample consists of 100 respondents selected using a purposive sampling technique based on predetermined criteria. Data were collected through structured questionnaires and analyzed using multiple linear regression analysis with the assistance of SPSS version 22. The stages of analysis included validity testing, reliability testing, normality testing, linearity testing, and multicollinearity testing. Hypothesis testing was conducted through simultaneous testing (F-test) and partial testing (t-test). The results indicate that simultaneously, product quality, promotional mix, and location have a positive and significant effect on customer satisfaction. Partially, product quality, promotional mix, and location are also proven to have a positive and significant effect on customer satisfaction. These findings indicate that improving product quality, enhancing promotional effectiveness, and selecting a strategic location are important factors in increasing customer satisfaction in the culinary business.